The study of some phenotype and physiological characteristic of water hyacinth Eichhornia crassipes (Mart.) Solms-Laubach on different regions of Thi-qar governorate - Sabah N. Nasir; Alyaa Hussein Talib; Suham Z. Manshad; Abdul -Wahab R. Ayyal (University of Thi-Qar Journal of agricultural research, 2020)
The plant of water hyacinth Eichhornia crassipesis an abundant floating aquatic weed that has great potential for reproduction in Iraq especially at Thi-Qar governorateat last years, So the study was conducted on plant at three different regions to know the differences on some phenotypic characters are ( plant high , root longs , number of leaves , leaf area and the fresh and the dry weights of leaves ) . The results were revealed a clear difference at plant high , root longs , number of leaves , leaf area , fresh and dry weights of plant shoots , also concentrations of chlorophyll , carotenoids , carbohydrates and proteins were estimated . It was found that a clear difference on the concentrations of the components that were studied .